Amenable mortality as a performance indicator of Italian health-care services - Fantini Maria P; Lenzi Jacopo; Franchino Giuseppe; Raineri Cristina; Burgio Alessandra; Frova Luisa; Domenighetti Gianfranco; Ricciardi Walter; Damiani Gianfranco (BMC, 2012)
Abstract Background Mortality amenable to health-care services ('amenable mortality') has been defined as "premature deaths that should not occur in the presence of timely and effective health care" and as "conditions for which effective clinical interventions exist." We analyzed the regional variability in health-care services using amenable mortality as a performance indicator. Convergent validity was examined against other indicators, such as health expenditure, GDP per capita, life expectancy at birth, disability-free life expectancy at age 15, number of diagnostic and laboratory tests per 1,000 inhabitants, and the prevalence of cancer and cardiovascular diseases. Methods Amenable mortality rate was calculated as the average annual number of deaths in the population aged 0-74 years per 100,000 inhabitants, and it was then stratified by gender and region. Data were drawn from national mortality statistics for the period 2006-08. Results During the study period (2006-08), the age-standardized death rate (SDR) amenable to health-care services in Italy was 62.6 per 100,000 inhabitants: 66.0 per 100,000 for males and 59.1 per 100,000 for females. Significant regional variations ranged from 54.1 per 100,000 inhabitants in Alto Adige to 76.3 per 100,000 in Campania. Regional variability in SDR was examined separately for male and females. The variability proved to be statistically significant for both males and females (males: Q-test = 638.5, p < 0.001; females: Q-test = 700.1, p < 0.001). However, among men, we found a clear-cut divide in SDR values between Central and Southern Italy; among women, this divide was less pronounced. Amenable mortality was negatively correlated with life expectancy at birth for both genders (male: r = −0.64, p = 0.002; female: r = −0.88, p <0.001) and with disability-free life expectancy at age 15 (male: r = −0.70, p <0.001; female: r = −0.67, p <0.001). Amenable mortality displayed a statistically significant negative relationship with GDP per capita, the quantity of diagnostic and laboratory tests per 1,000 inhabitants, and the prevalence of cancer. Conclusions Amenable mortality shows a wide variation across Italian regions and an inverse relationship with life expectancy and GDP per capita, as expected.